FUSULINID SEQUENCE EVOLUTION AND SEQUENCE EXTINCTIONIN WOLFCAMPIAN AND LEONARDIAN SERIES (LOWER PERMIAN),GLASS MOUNTAINS, WEST TEXAS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
In the Permian Wolfcampian and Leonardian Series of West Texas, sequence evolution and sequence extinction record the appearance and disappearance of morphological species in stratigraphic successions that show repeated sea level fluctuations and associated depositional hiatuses. The lower Wolfcampian Nealian Stage includes 16 relatively short term sea-level fluctuations (fourth-order depositional sequences) and contains a diverse fusulinid fauna of more than 39 species and eight genera.  Most Nealian species range through three or four fourth-order cycles before becoming extinct and none extends into the overlying upper Wolfcampian Lenoxian Stage.  The succeeding Lenox Hills Formation overlies a tectonic unconformity (and hiatus) and includes three third-order depositional sequences.  Four Lenoxian species are restricted to the lower sequence, 16 to the middle sequence, and six to the upper sequence. In the Leonardian Series, at the base, the Hessian Stage includes seven third-order depositional sequences and numerous minor fourth-order and smaller parasequences.  Hessian carbonate platform facies have low fusulinid species diversity and high abundances.  The lower four Hessian lowstand clastic wedges of the shelf margin and basin include at least six species of schwagerinids.  The three upper wedges include only three species of Parafusulina. The Cathedralian (upper) Stage has one main third-order depositional sequence, and perhaps a second, which is mostly missing on the platform below the Mid-Permian unconformity below the Middle Permian Guadalupian Series. Suggested correlations of the Wolfcampian and Leonardian with the Tethyan succession in Darvas and the Pamirs of Middle Asia place the Nealian as equivalent to the Asselian and Sakmarian. The Lenoxian is probably equivalent to the lower and middle parts of the Yakhtashian.  The Hessian is equivalent to the upper part of the Yakhtashian and the Bolorian. The Cathedralian seems to be equivalent to the Kubergandian. There is little evidence that the upper part of the Kubergandian extends higher into the Middle Permian Roadian Stage.